Meritocracy In The Correspondence Of Prophet Muhammad PBUH - Firdaus, Danang; Ichwan, Mohammad Nor (Tasamuh: Jurnal Studi Islam, 2025)
This study addresses the critical phenomenon of leadership incompetence resulting from appointments based on popularity and personal proximity, examining the correspondence of the Prophet Muhammad as a historical model of meritocratic selection. The research objective is to identify selection criteria for envoys, including linguistic competence, cross-cultural experience, and integrity, and assess how prophetic practices can inform contemporary recruitment reform. A qualitative library-based methodology with a historical approach and triangulation of primary sources and secondary literature was employed. Thematic analysis of sirah manuscripts and variant reports reveals selection patterns emphasizing functional capability and the companions’ work ethic. Findings confirm that successful diplomatic missions relied on a synergy between technical competence and moral character among envoys. Recommendations include combining procedural merit mechanisms with character development programs and transparent selection processes to curb patronage. The study offers guidance for selection audits, publishing criteria, evidence-based evaluation, and local capacity building.